Erasing Frankenstein: remaking the monster, a public humanities prison arts project - Effinger, Elizabeth (Life writing series, 2024)
"Erasing Frankenstein showcases a creative exchange between federally incarcerated women and members of the prison-education think tank Walls to Bridges Collective at the Grand Valley Institution for Women (GVI) in Kitchener, Ontario, and graduate and undergraduate students from the University of New Brunswick (UNB) in Fredericton, New Brunswick. Working collaboratively by long-distance mail, the artists and contributors made the first-ever poetic adaptation of Frankenstein, turning it into a book-length erasure poem. An erasure poem is an example of "found art," a poem created by piggybacking on an existing text; the words that are not part of the poem are erased or blacked out, and what is left is the poem. This book presents the original erasure poem alongside reflections from participants on the experience."--